Revisão sistemática dos fatores causais de baixa autoestima em indivíduos com acidente vascular encefálico - Silva, Renan Alves (2019)
Individuals affected by stroke are predisposed to have low self-esteem. However, there is a gap in the scientific production of synthesis with respect to the causal factors and the magnitude of the effect of these factors in the referred population under study. Therefore, it is proposed to analyze the evidence produced on the causal factors of Low self-esteem in adults and elderly individuals with stroke. A systematic review was carried out with the following guiding question: What are the measures of magnitude of effect of the causal factors of Low self-esteem in adults and elderly individuals with stroke? The review was developed according to the Joanna Briggs Institute reviewer manual, in the databases: PubMed, CINAHL, PsycoINFO, Scopus, Cochrane, Joanna Briggs Institute Data Base, LILACS, in English, Portuguese and Spanish. The descriptors contained in the search protocol were: self esteem, stroke, situational, chronic, low, factor, epidemiologic factors, precipitating factors, causality, risk factors. Inclusion criteria were the description of causal factors of low self-esteem among adults and elderly people affected by stroke. The sample was composed mainly of observational studies. Data analysis took place in three stages until the final sample of articles was obtained by two reviewers, independently. The methodological quality of the articles was verified using the Joanna Briggs Institute tools. Thus, the systematic review included 18 studies, in which, high methodological quality was observed. There was a causal relationship between low self-esteem and demographic variables, injury variables, chronic conditions, sleep behaviors, cognitive functioning, functional independence, inconsistent behaviors in relation to values, body image, emotional well-being. It was observed that, among the associated factors, four were possible to undergo the meta-analysis technique for meeting the synthesis criteria: depressive state (OR = 4.21; CI = 2.72-6.53); deficit in self-care of basic activities of daily living (OR = 7.61; CI = 2.63-21.99); impaired mood (OR = 6.37; CI = 4.06-9.99) and impaired physical mobility (OR = 4.33; CI = 1.07-17.52). Impaired physical mobility and deficit in self-care of basic activities of daily living act as precipitating factors; Impaired mood was understood in this study as a disabling factor and the depressed state acts as a predisposing factor for Low self-esteem. Impaired physical mobility and deficit in self-care of basic activities of daily living are recognized by NANDA-I as the condition associated with functional impairment. However, impaired mood and depressed state are not part of the current structure of taxonomy. Although no studies of nursing diagnoses were found in this review, their results contribute to the refinement of the diagnoses Low situational self-esteem and Chronic low self-esteem. Results were found that confirm related factors and associated conditions present in the taxonomy. Impaired mood and depressed state must be verified by other studies for later incorporation into the NANDA-I taxonomy.